1995
DOI: 10.1002/eji.1830251103
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I‐restricted CD8+ T cells and class II‐restricted CD4+ T cells, respectively, mediate and regulate contact sensitivity to dinitrofluorobenzene

Abstract: Contact sensitivity (CS) is a form of delayed‐type hypersensitivity to haptens applied epicutaneously and is thought to be mediated, like classical delayed‐type hypersensitivity responses, by CD4+ T helper‐1 cells. The aim of this study was to identify the effector T cells involved in CS. We studied CS to the strongly sensitizing hapten dinitrofluorobenzene (DNFB) in mice rendered deficient by homologous recombination in either major histocompatibility complex (MHC) class I, MHC class II, or both, and which ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
192
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(226 citation statements)
references
References 34 publications
22
192
0
11
Order By: Relevance
“…Subsequent studies in mice by Gosinski and Tigelaar (9) and repeated by this laboratory (10) demonstrated that depletion of CD4 ϩ T cells before hapten sensitization resulted in CHS responses of high magnitude and long duration, whereas depletion of CD8 ϩ T cells resulted in either absent or reduced CHS responses. Similar results were observed using MHC class I and class II knockout mice as models of CD8 ϩ and CD4 ϩ T cell deficiencies, respectively (11). In vitro analyses of hapten-primed T cells indicated that sensitization for CHS induces two distinct polarized populations of hapten-reactive T cells: CD8 ϩ T cells that produce IFN-␥ in response to hapten stimulation and hapten-specific CD4 ϩ T cells that produce IL-4, IL-5, and IL-10 and little or no IFN-␥ (10).…”
supporting
confidence: 84%
“…Subsequent studies in mice by Gosinski and Tigelaar (9) and repeated by this laboratory (10) demonstrated that depletion of CD4 ϩ T cells before hapten sensitization resulted in CHS responses of high magnitude and long duration, whereas depletion of CD8 ϩ T cells resulted in either absent or reduced CHS responses. Similar results were observed using MHC class I and class II knockout mice as models of CD8 ϩ and CD4 ϩ T cell deficiencies, respectively (11). In vitro analyses of hapten-primed T cells indicated that sensitization for CHS induces two distinct polarized populations of hapten-reactive T cells: CD8 ϩ T cells that produce IFN-␥ in response to hapten stimulation and hapten-specific CD4 ϩ T cells that produce IL-4, IL-5, and IL-10 and little or no IFN-␥ (10).…”
supporting
confidence: 84%
“…A general model in which CD8 π T lymphocytes act as effectors, while allergen-specific CD4 π cells perform regulatory functions, is supported by various investigations using mice. For instance, based on an understanding of differential major histocompatibility complex (MHC) class restriction of CD4 π and CD8 π T lymphocytes, it was shown that mice lacking MHC class I were unable to support CHS responses to the contact allergen dinitrofluorobenzene (DNFB), whereas MHC class II-deficient mice exhibited an exaggerated CHS reaction (25); a reaction shown subsequently to be mediated by CD8 π T lymphocytes (26). Consistent with these data are the results of other investigations in which it was found that MHC class I π /II -DC were able to prime for contact hypersensitivity, but MHC class I -/II π DC were not (27,28).…”
Section: Cd8 π Effector Cells and Interplay With Cd4 π Cellsmentioning
confidence: 99%
“…Recently, a CD4 + CD25 + subset has been identified that is characterized by its ability to suppress T cell proliferation in vivo and in vitro. These "naturally occurring" CD4 + CD25 + regulatory T cells (Treg), which express the a chain of the IL-2 receptor, originate from the thymus [5,6] and represent 5-10% of the adult peripheral CD4 + T cells in normal naive mice. It is well established that Treg participate in the maintenance of immunological self-tolerance and the regulation of immune responses to non-self antigens [7].…”
Section: Introductionmentioning
confidence: 99%